Syntactical Analytical Overview of the New Testament Translation by Vangjel Meksi, After the Editing of Grigor of Gjirokastra, Focusing on the Syntax and the Sentence Types Strata - Bramo, Elvis (European Journal of Multidisciplinary Studies, 2018)
In this paper, we have focused the study on the sintactical level of the translation of New Testament by Vangjel Meksi Laboviti, after the editing of Grigor of Gjirokastra, focusing mostly on syntactical units which are syntagms, as well as their constituents. In the core of the young scholar Bramo, it is the investigation on the syntactical units-syntagms: their connection, types, heads and relations of these connections in sentences. The schemes shown by Mr. Bramo show the high number of syntagmatic connections and the richness of means Albanian language owns, provided by the translators of the New Testament, according to the nature of our native language. The paper, contains a theoretical ground with authors and works from the generative linguistics school, basing on those contractions that can be integrated in syntagmatic structures and connections with models of our language.